Justification for the freedom of selfconsciousness in the work «Phenomenology of spirit» by G. W. F. Hegel - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
It is shown that G. W. F. Hegel trusts his «Phenomenology of spirit» an extremely important systemic function, which, in fact, determines the place of this work in the teachings of the German philosopher. Its presentation not only precedes its entire subsequent three-part system, but is also a prerequisite for it, which should justify freedom of self-consciousness. It is here that G. W. F. Hegel will set as his main task to overcome the phenomenality of consciousness, to liberate him from an object form alien to him. Thus, he will try, and unsuccessfully, to establish the principle of the identity of being and thinking, which will be fundamental to his entire subsequent philosophical system.
Keywords: G. W. F. Hegel; «Phenomenology of spirit»; self-consciousness; freedom of self-consciousness; the negative function of phenomenology; the history of the self-liberation of consciousness